PECULIARITIES OF ASYMMETRIC REINFORCED CONCRETE HIGH-RISE BUILDINGS AND THEIR DESIGN - Lia Balanchivadze; Beqa Matitaishvili (Progress in Science, 2024)
Tall buildings are unique in terms of architecture, construction, construction technology, operation and reliability and are a symbol of the country’s strength and technological progress. They belong to the facilities around the world that have the highest level of responsibility and reliability.